2008
DOI: 10.1523/jneurosci.3080-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hippocampal GluR1 and GluR2 Receptors in Manic-Like Behavior

Abstract: The cellular basis underlying the complex clinical symptomatology of bipolar disorder and the mechanisms underlying the actions of its effective treatments have not yet been fully elucidated. This study investigated the role of hippocampal synaptic AMPA receptors. We found that chronic administration of the antimanic agents lithium and valproate (VPA) reduced synaptic AMPA receptor GluR1/2 in hippocampal neurons in vitro and in vivo. Electrophysiological studies confirmed that the AMPA/NMDA ratio was reduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
72
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 59 publications
9
72
0
1
Order By: Relevance
“…Protein concentrations were determined by using the BCA protein assay kit (Pierce, Rockford, IL). Western blot analysis was similar to a previously published procedure with minor modifications (29,30). Detailed methods are provided in the SI.…”
Section: Preparation Of Mitochondrialmentioning
confidence: 99%
“…Protein concentrations were determined by using the BCA protein assay kit (Pierce, Rockford, IL). Western blot analysis was similar to a previously published procedure with minor modifications (29,30). Detailed methods are provided in the SI.…”
Section: Preparation Of Mitochondrialmentioning
confidence: 99%
“…In addition, recent studies found that the hippocampus is involved in dopaminergic signaling circuits, and that the ventral subiculum of the hippocampus modulates dopaminergic neuronal activity (33,34). Rats receiving hippocampal infusion of the AMPA-specific antagonists GYKI 52466, Tat-S845 (which inhibits GluR1 phosphorylation at S845), or TAT-TGL (which inhibits AMPA synaptic localization) exhibited significant reductions in AMPH-induced locomotion (7). In the present study, the inhibition of AMPAR internalization in hippocampal neurons by GSK-3 may have contributed to the increased surface GluR1 levels in hippocampal neurons.…”
Section: Gsk-3 Regulation Of Ampar Trafficking As a Mechanism For Affmentioning
confidence: 99%
“…Accumulating studies from our laboratory and those of other investigators have shown that glutamatergic synaptic plasticity, particularly α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate receptor (AMPAR) trafficking, may be a convergent point in the treatment of mood disorders (7)(8)(9)(10). For instance, rats receiving hippocampal infusions of AMPA-specific inhibitors exhibited significant reductions in manic-like behaviors assessed through the AMPH-induced locomotion (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GluR1/2 heteromers are the major receptor type within the hippocampus and increases in activity and numbers of both subunits are associated with manic-like behavior (Wenthold et al 1996;Du et al 2008). When expressed in mammalian cell lines the homomeric GluR1/2 exhibits a non-rectifying current-voltage (I-V) relationship and differ from the GluR1 homomers in their lower permeability to Ca 2+ .…”
Section: Glutamate Receptor I (Glur1)mentioning
confidence: 99%